Women, historiography and oral history: a possible dialogue (Research, Society and Development, 2020)
This work brings some considerations about the history of women and the changes that happened in the historiographic field, as well as their relationship with oral history, which allows us to understand that through orality the subject meets and re-encounters with the historical and social context. Thinking about the history of women leads us to a history in which, for centuries, women were viewed in a subordinate way, being excluded from educational and social processes, silenced to the point of doubting whether they were in fact part of the construction of history of humanity. Given the above, we will use a bibliographic research, seeking theoretical foundations that help us understand the emergence of a conception that starts to consider women as active subjects in history. The results show the historiographical contributions to the reconstruction in the history of women, the moment when we started to consider other perspectives that do not aim only at the history of great male personalities of the past. Oral history features its democratic aspect, and allows women to find yet another path capable of echoing their voice, silenced for centuries.